Baicalin Attenuates Oxygen–Glucose Deprivation/Reoxygenation–Induced Injury by Modulating the BDNF-TrkB/PI3K/Akt and MAPK/Erk1/2 Signaling Axes in Neuron–Astrocyte Cocultures - Li, Changxiang; Sui, Conglu; Wang, Wei; Yan, Juntang; Deng, Nan; Du, Xin; Cheng, Fafeng; Ma, Xiaona; Wang, Xueqian; Wang, Qingguo (Frontiers in Pharmacology, 2021)
Background: Baicalin (BCL), a candidate drug for ischemic stroke, has been indicated to protect neurons by promoting brain-derived neurotrophic factor (BDNF). However, the cellular source of BDNF release promoted by baicalin and its detailed protective mechanism after ischemia/reperfusion remains to be studied. The aim of this study was to investigate the neuroprotective mechanisms of baicalin against oxygen–glucose deprivation/reoxygenation (OGD/R) in a neuron–astrocyte coculture system and to explore whether the BDNF-TrkB pathway is involved. Methods and Results: A neuron–astrocyte coculture system was established to elucidate the role of astrocytes in neurons under OGD/R conditions. The results demonstrated that astrocytes became reactive astrocytes and released more BDNF in the coculture system to attenuate neuronal apoptosis and injury after OGD/R. BCL maintained the characteristics of reactive astrocytes and obviously increased the expression of cyclic AMP response element-binding protein (CREB) and the levels of BDNF in the coculture system after OGD/R. To further verify whether BDNF binding to its receptor tyrosine kinase receptor B (TrkB) was required for the neuroprotective effect of baicalin, we examined the effect of ANA-12, an antagonist of TrkB, on NA system injury, including oxidative stress, inflammation, and apoptosis induced by OGD/R. The results showed that treatment of NA systems with ANA-12 significantly attenuated the neuroprotection of BCL. The phosphatidylinositol 3-kinase (PI3K)/protein kinase B (Akt) and mitogen-activated protein kinase (MAPK)/extracellular signal-regulated kinase (ERK) pathways are two important downstream cascades of signaling pathways activated by BDNF binding to TrkB. We investigated the expressions of TrkB, PI3K, Akt, MAPK, and ERK. The results demonstrated that baicalin significantly increased the expressions of TrkB, PI3K/AKT, and MAPK/ERK. Conclusion: The neuroprotective effects of baicalin against oxidative stress, inflammation, and apoptosis were improved by astrocytes, mainly mediated by increasing the release of BDNF and its associated receptor TrkB and downstream signaling regulators PI3K/Akt and MAPK/ERK1/2.